The role of starter cultures on oral processing properties of different fermented milk products. (May 2021) - Buldo, Patrizia; Sokolowsky, Martina; Hoegholm, Tina
Abstract: Oral processing of food is a complex and highly dynamic process as the physical properties of foods change continuously when they are manipulated in the mouth. Texture and mouth feeling are important drivers of liking for fermented milk products and therefore are of high interest in the product development. The textural properties of fermented milk can be manipulated by ingredients, including starter cultures, and production process. The bulk texture of fermented milk products is often not a good indicator of some mouthfeel properties, such as smoothness and mouth coating. Tribology approaches are increasing due to their ability to better describe the mechanical oral processing, when compared to rheological measurements. In the present study, the role of starter cultures, on the lubricating and mouthfeel properties of different types of fermented fresh dairy products was studied, using the examples: stirred and concentrated yoghurt, quark and post-pasteurized ambient yoghurt (PPAY). Oral processing and mouthfeel properties were analyzed with a ball on three pins tribometer and by descriptive sensory analysis, respectively. The complexity revealed by the oral processing properties measured via friction coefficient (FC) indicates a product, hence microstructure, dependency. This was reflected by the five curves shape identified. Independently from the curve shape, the selected FCs negatively correlated to mouth thickness and mouth coatings for all studied products. In the case of fatty, grainy, powdery or slimy products, as for quark and PPAY, negative correlations with the selected FCs were identified. The present study highlights the effect of starter cultures on improving the mouthfeel properties of fermented milk products by using a novel approach as tribology. Graphical abstract: Image 1 Highlights: Cultures contribute to mouth -thickness and coating, fatty feeling and smoothness. Tribology can be used to quantify oral processing properties in fermented products. Tribology measurements identified 5 curves shapes in fermented dairy products. Physical measurements are product, hence microstructure dependent. The above needs to be considered when predicting sensory properties.